Contributions to the Naarda Walker, 1866 (Lepidoptera: Erebidae, Hypeninae) fauna of Thailand, with the description of a new species. (3rd April 2019) - Tóth, Balázs
ABSTRACT: Twenty species of Naarda Walker has been hitherto found in Thailand; all of them are listed in this work with reference to their first record from this country. Three species: N. inouei Tóth & Ronkay; N. lancanga Deng & Han and N. kinabaluensis Holloway are found for the first time in Thailand and their external habitus and genitalia are illustrated. The formerly unknown female of N. lancanga is presented and a new species, N. straminea sp. n., is described. With 18 figures. http://zoobank.org/urn:lsid:zoobank.org:pub:ACD13EF3-C23F-44AE-801F-75C161B9B94D